Procedure to be followed by medical personnel in case of diagnosis of the Child Abuse Syndrome - Elżbieta Bernaciak; Magdalena Lemska; Magdalena Michalewicz; Helena Mirus-Arabik; Sandra Olwert (Kazimierz Wielki University, 2019)
Nowadays, there are more and more reports of child abuse. However, this is not due to an increase in violence against minors, but to an increase in public awareness. People have begun to report child abuse. Child Abuse Syndrome affects both physical and psychological violence. There are many risk factors. Correct diagnosis is difficult, especially for children who start walking, running and all kinds of injuries can be the result of their playing. Intelligence, accurate viewing of the child and physical examination has an important role. When discussing the child abuse syndrome, let's not forget about Munchausen syndrome per procura. Then the child's testimonies are invented, very often behind the story presented by the young patient there is a family member - mainlythe mother. Since September 2011, all health care workers are subject to the "Blue Card" procedure. [11,27] If child abuse has occurred in the family, or even if there is a suspicion of such abuse, an Interdisciplinary Team is established. The task of this team is to complete the Blue Card procedure and to ensure the safety of a victim of violence. A paramedic plays an important role in this procedure. In most cases it is the person who first comes into contact with a child who is a victim of abuse. The paramedic must ensure that the patient feels safe. Their task is to identify the problem, document the injuries occurring on the child's body at the time of examination and fill in the appropriate documentation, which will be handed over to the Interdisciplinary Team. This paper presents materials explaining the epidemiology and clinical image of the child abuse syndrome. Social aspects and legal consequences of this issue are also discussed. The "Blue Card" procedure and the "Blue Bear" form are also presented. The paper explains the role of medical personnel in case of violence against children.